Languages in Africa : Multilingualism, Language Policy, and Education - Kramer, Ruth (Ruth T.); Tlale Boyer, One; Zsiga, Elizabeth C. (Book collections on Project MUSE., 2014)
People in many African communities live within a series of concentric circles when it comes to language. In a small group, a speaker uses an often unwritten and endangered mother tongue that is rarely used in school. A national indigenous language-written, widespread, sometimes used in school-surrounds it. An international language like French or English, a vestige of colonialism, carries prestige, is used in higher education, and promises mobility-and yet it will not be well known by its users. The essays in Languages in Africa explore the layers of African multilingualism as they affect lang.